Impact of non-petroleum vehicle fuel economy on GHG mitigation potential - Jason M Luk; Bradley A Saville; Heather L MacLean (Environmental Research Letters, 2016)
The fuel economy of gasoline vehicles will increase to meet 2025 corporate average fuel economy standards (CAFE). However, dedicated compressed natural gas (CNG) and battery electric vehicles (BEV) already exceed future CAFE fuel economy targets because only 15% of non-petroleum energy use is accounted for when determining compliance. This study aims to inform stakeholders about the potential impact of CAFE on life cycle greenhouse gas (GHG) emissions, should non-petroleum fuel vehicles displace increasingly fuel efficient petroleum vehicles. The well-to-wheel GHG emissions of a set of hypothetical model year 2025 light-duty vehicles are estimated. A reference gasoline vehicle is designed to meet the 2025 fuel economy target within CAFE, and is compared to a set of dedicated CNG vehicles and BEVs with different fuel economy ratings, but all vehicles meet or exceed the fuel economy target due to the policy’s dedicated non-petroleum fuel vehicle incentives. Ownership costs and BEV driving ranges are estimated to provide context, as these can influence automaker and consumer decisions. The results show that CNG vehicles that have lower ownership costs than gasoline vehicles and BEVs with long distance driving ranges can exceed the 2025 CAFE fuel economy target. However, this could lead to lower efficiency CNG vehicles and heavier BEVs that have higher well-to-wheel GHG emissions than gasoline vehicles on a per km basis, even if the non-petroleum energy source is less carbon intensive on an energy equivalent basis. These changes could influence the effectiveness of low carbon fuel standards and are not precluded by the light-duty vehicle GHG emissions standards, which regulate tailpipe but not fuel production emissions.